Pengembangan Aplikasi Adopsi Hewan Kucing Berbasis Website - David Septianto; Paramaresthi Windriyani (UNIVERSITAS KALBIS, 2022)
This study aims to assist adopters in the process of adopting and adopting cats. In this study, developing a cat animal adoption application using a bootstrap framework technology, PHP, and MySQL based on a website. The development method used is the Rational Unified Process (RUP) which consists of four stages, namely, inception, elaboration, construction, and transition. Application development is equipped with features to view adopted animal albums, upload animals that you want to adopt, want to adopt animals, archives of adopted or released animals, and archives of adopted animals. This research uses XAMPP software, Sublime Text 3, and uses the PHP programming language. The result of this application is in the form of a website.